Dimensi - Agustiawan, Agustiawan; Halim, Abdul (Akuntansi & Ekonomika, 2018)
This study aims to find out how the influence of the dimensions of accountability and performance of public sector organizations. The accountability dimensions used in this study consist of performance accountability, financial accountability, hierarchical accountability, professional accountability and legal accountability. Performance in this research is quantitative performance and qualitative performance. This research is a qualitative research to answer the research questions proposed by using semi-structured and open interviews by using thematic content analysis method. The results of this study indicate that financial accountability, performance accountability, legal accountability, hierarchical accountability and professional accountability affect the performance of public sector organizations.  Inplinsit that institutional isomorphism occurs in public sector organizations. Keywords: Accountability, Performance.